The Science of Truth: Science in Efforts to Maintain the Balance of Nature - Wawan, Eko Setiyo (AGARICUS: Advances Agriculture Science & Farming, 2024)
Science in the digital era is currently developing very rapidly, but in an effort to keep humans able to implement science, science in an effort to maintain the balance of nature requires some understanding so that the context is carried out in line with Islamic teachings and the guidance of the Koran. There are several questions that will later be known about the nature of the truth of science in an effort to balance nature, namely how is the truth as long as humans recognize the creator in all of his creations which later on is a reality that we can recognize/that we can think about/that we can explain and that we can live. . Islamic Suggestions in Seeking Knowledge and Truth Through Communication of Al-Quran verses, Islam is a religion that covers all aspects of human life. Al-Quran is a guide to humans how a Muslim should live his life from birth to death. With the basis of Islam and the Qur'an, the development of science, science in an effort to maintain the balance of nature which requires us to play a role in it is a logical truth and can be used in social life dynamically and peacefully for the benefit of the people